Analisis Defect Produk Ring Piston pada Line B- Ken Melalui Pengendalian Kualitas dengan Metode Six Sigma di PT XYZ - Wijaya, Hadi; Maulidani, Bagas Caesar; Romli, Ikhsan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze defect rates of ring piston products on Line B-KEN at PT XYZ and formulate quality improvement recommendations using the Six Sigma method. High defect rates, such as cracks, undersize, and oversize, directly impact quality costs and productivity. This applied research employs a quantitative approach through the DMAIC cycle (Define, Measure, Analyze, Improve, Control). Data were collected from 2021–2024 production records, field observations, and interviews. DPMO calculations indicate that process capability is not yet optimal, with cracks identified as the dominant defect. Pareto and fishbone diagram analyses reveal that human, machine, method, and material factors are the primary root causes. Proposed improvements include SOP standardization, operator training, machine parameter control, and strengthened process supervision. Implementing these strategies is expected to reduce defect rates and enhance sustainable production stability.